Measuring Verbal Fluency Task Performance of Indonesian Bilinguals - Feisal Aziez; Hazim Alkhrisheh; Furqanul Aziez; Maulana Mualim (Indonesian Research Journal in Education |IRJE|, 2020)
Verbal fluency (VF) task is a tool that has been utilized in bilingual studies to measure executive performance of bilingual individuals. While many of the previous studies compared bilingual speakers’ performance in VF to their monolingual counterparts, this descriptive study compares exclusively the cross-linguistic VF performance of Indonesian bilinguals in their first (L1), second (L2), and third language (L3). The aim of this study was to see whether or not there were any differences in the result of their performance in each of their languages. The participants of the current study were 25 non-native bilingual university students in Indonesia who speak English in at least intermediate level. Javanese is the L1 of the participants. Indonesian is their L2, whereas English is their L3. In the VF task, the participants were requested to generate, in a rapid fashion, semantic category and phonemic category in their L1, L2, and L3. The results showed that the participants’ VF performance in English and standard Indonesian were significantly higher (p < .05) than Javanese. However, no significant difference was indicated when comparing the semantic category and phonemic category in all three languages. The findings of this study will be used as a basis for a forthcoming study on VF performance of Indonesian bilinguals.